Pengaruh Pembiayaan Bank Syariah, dan Tenaga Kerja Terhadap PDRB Jawa Barat - Ryhan Firdausy Noor Dermawan; Mochamad Edman Syarief; Kristianingsih Kristianingsih (Indonesian Journal of Economics and Management, 2022)
This study aims to analyze the effect of Islamic bank financing and labor on the economy of West Java as seen from the GRDP of West Java. Based on its nature, this research is associative because it aims to determine the effect of two or more variables. Sampling in this study used a purposive sampling method with secondary data obtained from Islamic Banking Statistics published by the Financial Services Authority, statistics published by the Central Bureau of Statistics, and other data related to the subject and object of the study. This research uses Path Analysis method. This study is expected to be able to see the relationship between the independent variables, namely Islamic bank financing, the intervention variable, namely labor, then West Java's Gross Regional Domestic Product (GRDP) as the dependent variable. The results of this study indicate that the variable of Islamic bank financing has an effect on the GRDP of West Java, as well as that of Islamic bank financing and labor have an effect on the GRDP of West Java. The findings of this study contribute to Islamic banking and the West Java government as a reference for improving the economy.